2020
DOI: 10.1038/s41598-020-75651-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a clinical score to estimate progression to severe or critical state in COVID-19 pneumonia hospitalized patients

Abstract: The prognosis of a patient with COVID-19 pneumonia is uncertain. Our objective was to establish a predictive model of disease progression to facilitate early decision-making. A retrospective study was performed of patients admitted with COVID-19 pneumonia, classified as severe (admission to the intensive care unit, mechanic invasive ventilation, or death) or non-severe. A predictive model based on clinical, laboratory, and radiological parameters was built. The probability of progression to severe disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
4
19
0
1
Order By: Relevance
“…In this retrospective analysis of 1,108 hospitalized COVID-19 patients at an epicenter during the first wave of the pandemic, we were able to identify risk factors and associations with mortality. Consistent with previous reports, we observed that increasing age and certain pre-existing medical conditions relating to major organ systems were associated with increased chance for death [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…In this retrospective analysis of 1,108 hospitalized COVID-19 patients at an epicenter during the first wave of the pandemic, we were able to identify risk factors and associations with mortality. Consistent with previous reports, we observed that increasing age and certain pre-existing medical conditions relating to major organ systems were associated with increased chance for death [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…For comparison with CT we considered several established blood biomarkers of severity of COVID-19 pneumonia including serum LDH, D-dimer, CRP and lymphocyte counts that can predict ICU admission (10,12,13,15,16,23). As well, we considered the P/F ratio which is a marker of non-responsive hypoxiemia in these patients (10,14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Hence prediction of ICU admission has been frequently investigated in studies addressing diagnostic and prognostic models for COVID-19 (5). Among the variables potentially useful for such a purpose, clinical features yielded mixed results (6)(7)(8)(9)(10)(11)(12), while blood laboratory and arterial gas analysis features generally improved the overall prediction capacity (8,10,11,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with CT we considered several established blood biomarkers of severity of COVID-19 pneumonia including serum LDH, D-dimer, CRP and lymphocyte counts that can predict ICU admission 10 , 12 , 13 , 15 , 16 , 24 . As well, we considered the P/F ratio which is a marker of non-responsive hypoxiemia in these patients 10 , 14 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence prediction of ICU admission has been frequently investigated in studies addressing diagnostic and prognostic models for COVID-19 5 . Among the variables potentially useful for such a purpose, clinical features yielded mixed results 6 12 , while blood laboratory and arterial gas analysis features generally improved the overall prediction capacity 8 , 10 , 11 , 13 16 .…”
Section: Introductionmentioning
confidence: 99%